2016
DOI: 10.1080/03721426.2016.1196473
|View full text |Cite
|
Sign up to set email alerts
|

Impact of foxes digging for the pygmy bluetongue lizard (Tiliqua adelaidensis)

Abstract: The endangered pygmy bluetongue lizard (Tiliqua adelaidensis) is endemic to heavily fragmented patches of native grassland in the mid-north region of South Australia. The lizards live in spider burrows, and suitable burrows can be a limiting factor to local populations. The invasive red fox (Vulpes vulpes) is a likely predator of the lizards. No previous research has focussed on the effects of foxes on pygmy bluetongue lizards. This article presents observations from three sampling rounds in a single lizard ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The snakeeyed lizard Ophisops elegans has been reported to be distributed within an area ranging from southern and western Europe, Turkey and northern and eastern Asia to northern Africa (Oraie et al 2014). Reptiles are hunted by various raptors, some predatory mammals and poultry, and therefore, the investigation of the pathogens carried by these animals bears significance with respect to protecting the health of wild animals, humans and domestic animals (Bakaloudis et al 2012, Nielsen andBull 2016). To date, many studies have demonstrated bacterial agents including Salmonella spp., E. coli and Clostridium spp.…”
Section: Introductionmentioning
confidence: 99%
“…The snakeeyed lizard Ophisops elegans has been reported to be distributed within an area ranging from southern and western Europe, Turkey and northern and eastern Asia to northern Africa (Oraie et al 2014). Reptiles are hunted by various raptors, some predatory mammals and poultry, and therefore, the investigation of the pathogens carried by these animals bears significance with respect to protecting the health of wild animals, humans and domestic animals (Bakaloudis et al 2012, Nielsen andBull 2016). To date, many studies have demonstrated bacterial agents including Salmonella spp., E. coli and Clostridium spp.…”
Section: Introductionmentioning
confidence: 99%